A Literature Review of Recent Advances and Future Trends in Modern Drilling and Completion Technologies - Fu, Hongyuan (International Journal of Natural Resources and Environmental Studies, 2026)
In recent years, CNPC’s operating companies have carried out intensive R&D programs to address key bottlenecks that limit drilling efficiency and well construction performance, including rate-of-penetration (ROP) improvement for horizontal wells, deep-well drilling, casing-exit sidetracking for mature wells, and wellbore strengthening and loss-circulation control. Through targeted technology breakthroughs and systematic integration of mature practices, a series of distinctive, field-proven technology packages has been developed. The main advances reviewed in this paper include: (i) one-run drilling enabled by an integrated “four-in-one” bottom-hole assembly (BHA); (ii) deep formation ROP improvement technologies for the Cambrian and Changcheng (Great Wall) formations; (iii) “aggressive drilling” practices for ROP optimization; (iv) 3D horizontal-well profile design and the “pre-separation” anti-collision methodology for large pad drilling; (v) casing-window milling and sidetracked horizontal-well drilling and completion; (vi) drilling and completion for super-long horizontal laterals in tight-gas reservoirs; (vii) nitrogen drilling; (viii) wellbore pressure management (managed pressure drilling, MPD) techniques; (ix) slim-hole super-long horizontal drilling; and (x) specialized drilling-fluid systems. After several rounds of technological evolution, an integrated R&D framework characterized by a coordinated “process–tools–fluids” approach has been established. Looking forward, further efforts should be devoted to automation and intelligent drilling/completion, cost-effective development of tight and shale reservoirs, deep and ultra-deep drilling technologies, continuous upgrading of specialized drilling-fluid and environmental compliance technologies, and the development of integrated geo-engineering decision-making workflows. These innovations will support safe, efficient, and high-quality growth of China’s oil and gas industry.